Hexokinase Activator Attenuates Type 2 Diabetes Mellitus and Associated Endothelial Dysfunction in HFF-STZ-Induced Diabetic Rat: Pharmaceutical Science-Pharmacy - Patel, Ekta; Patel, Divyakant; Vegad, Kunjal; Patel, Yogesh; Shah, Priya; Shah, Dhwani; Kanzariya, Nilesh (International Journal of Life Science and Pharma Research, 2022)
Hexokinase is an enzyme involved in the glucose metabolism pathway. Magnesium is an inherent cofactor of the Hexokinase enzyme. The plethora of literature suggested that hexokinase level was decreased in diabetic rats. Sodium metavanadate shows insulin-mimetic action. We designed this work to determine the effect of magnesium on diabetes and associated vascular complications in rats. Type-2 diabetes was induced by a high-fat diet and a low dose of streptozotocin.. Diabetic rats were divided into groups, i.e. normal, diabetic, magnesium sulfate, sodium metavanadate, a combination of glibenclamide and metformin, a variety of sodium metavanadate with glibenclamide and metformin, and a combination of magnesium sulfate with glibenclamide and metformin. Magnesium sulfate was used as a hexokinase activator. Blood glucose levels were measured before initiation, between, and after 4 weeks of treatment. Biochemical and tissue parameters were estimated for additional confirmation. A vascular study took the contractile response of hydrogen peroxide in rat thoracic aortas of different groups. Statistical comparisons between groups were performed by two-tailed one-way ANOVA followed by the Dunnett test. P-values <0.05 were considered statistically significant. Treatment with magnesium sulfate and sodium metavanadate (S.M.V.) alone and in combination significantly (p<0.05) modified the elevated blood glucose and various altered biochemical parameters in diabetic rats. Treatment showed a significant decrease (p < 0.001) n elevated contractile responses of hydrogen peroxide in thoracic aortas of diabetic rats Vs Normal Control). Hexokinase activation by magnesium and sodium metavanadate significantly reduced (** p < 0.01) diabetes as well as vascular complications.